Microalgae-Based Wastewater Treatment as Green Solution for Sustainable Degradation and Its Challenges: A Review - Musifa, Eva; Palapa, Neza Rahayu; Ahadito, Bijak Riyandi (Indonesian Journal of Environmental Management and Sustainability, 2025)
Releasing polluted water directly into the environment causes serious problems because it contains harmful substances that can damage aquatic life and human health. To reduce these risks, it is important to treat and clean wastewater effectively. Microalgae have shown promise as a natural and sustainable way to treat wastewater. The microalgae help to remove pollutants and can also recover useful resources and energy from the water. The study used a systematic review methodology to identify and evaluate the role of microalgae wastewater treatment. The method was used since it provides a structures and transparent framework for selection, assessment and synthesize of evidence from relevant literature. This review highlights the benefits of using microalgae for wastewater treatment, as well as the challenges involved. Ongoing research focuses on improving these methods, including combining microalgae with bacteria to make the process more efficient and scalable. Despite some difficulties like contamination risks and regulatory issues, future advances especially in genetic engineering and hybrid systems are expected to improve microalgae-based wastewater treatment and make it a key tool for protecting the environment, while multidisciplinary collaboration combining molecular biology research, environmental engineering, public policy, and utilization of this technology at the industrial and societal levels that should be under consideration.